Ahmed Mohamed and the Imperial Necessity of Islamophilia. Issue 1 (1st October 2015) - Nazia Kazi
Abstract : In this article, I connect the arrest of clock-making youth Ahmed Mohamed in Irving, Texas to the U.S. carceral imperial state. I argue that his ordeal lies at the interstices of empire, race, and the school-to-prison pipeline, and I consider the ways in which Islamophilia – or "good Muslim" politics – serves as a veneer for persistent criminalization of youth of color, both through domestic procedures of policing as well as through global mechanisms of the U.S. war against terrorism. Based upon my fieldwork with Islamic representative organizations (IRO's), I show that the discourse on matters of inclusion and political change in the U.S. is deeply confined by colonialist contours of acceptability.